Rhodium(III)-Catalyzed Three-Component 1,2-Diamination of Unactivated Terminal Alkenes - Lee, Sumin; Jang, Young Jin; Phipps, Erik J. T.; Lei, Honghui; Rovis, Tomislav (Synthesis, 2020)
We report a three-component diamination of simple unactivated alkenes using an electrophilic nitrene source and amine nucleophiles. The reaction provides rapid access to 1,2-vicinal diamines from terminal alkenes through a one-pot protocol. The transformation proceeds smoothly with excellent tolerance for a broad array of primary and secondary amines, affording the desired products in good yield and regioselectivity. The mechanism is proposed to proceed through a Rh(III)-catalyzed aziridination of alkenes with subsequent ring opening by primary or secondary amines.
Keywords: alkene diamination; rhodium(III) catalysis; one-pot synthesis; nitrene